Nutritional Status of Children and Its Associated Factors in Selected Earthquake-Affected VDCs of Gorkha District, Nepal. (6th July 2020) - Shrestha, Asmita; Bhusal, Chet Kant; Shrestha, Binjwala; Bhattarai, Kiran Dev
Abstract : Background . Malnutrition is a major public health problem and most enveloping cause of morbidity and mortality among children and adolescents throughout the world. This study was aimed at assessing the nutritional status and associated factors among 6-10-year-old children in selected earthquake-affected areas of Gorkha district, Nepal. Methods . A community-based cross-sectional study among 420 mothers having children of age groups 6-10 years (with anthropometric measurement among children) was conducted using a mixed method in selected earthquake-affected areas of Gorkha district, Nepal, from October 2015 to April 2016. Gorkha was selected purposively from 14 earthquake-affected districts. Two village development committees were selected randomly among 6 having severe impact. Randomly, 5 wards were selected from each of the 2 village development committees. As the sample was 420, 42 children were selected randomly from every ward. Result . Among the 420 children, 31.9% were underweight, 51.9% were stunted, and 2.9% were wasted after the earthquake. Children who were more prone to being underweight were the following: male children (RR = 1.34 95% CI: 1.01-1.78) and children from illiterate mothers (RR = 2.49, 95% CI: 1.85-3.36), illiterate fathers (RR = 1.73, 95% CI: 1.32-2.27), and homemaker mothers (RR = 0.28, 95% CI: 0.20-0.38); children whose families were using nonimproved sources of water (RR = 2.60, 95% CI: 1.07-6.60); and households having food insecurity (RR = 12.97, 95% CI: 3.29-51.18). Similarly, children of illiterate fathers (RR = 1.67, 95% CI: 1.41-1.97), children of illiterate mothers (RR = 2.32, 95% CI: 1.91-2.83), children of homemaker mothers (RR = 0.59, 95% CI: 0.49-0.70), children whose family were using treated water (RR = 0.32, 95% CI: 0.15-0.67), and children from food insecure households (RR = 10.52, CI: 4.05-27.33) were found to be stunted. After adjustment, children from households consuming nonimproved water were 6 times more likely (OR = 6.75 ; 95% CI: 1.59-28.62) to be wasted. Conclusion . Illiterate mothers, illiterate fathers, mothers engaged in occupation other than household work, and food insecure households were found to be independent predictors of underweight and stunting. Nonimproved source of drinking water was found to be independent predictors of wasting.